Why Health Policy Reforms Fail: Implementation Barriers in South Africa’s National Health Insurance - Lesedi Senamele Matlala; Tshepo Mavhungu (OIDA International Journal of Sustainable Development, 2026)
Major public policy reforms in developing and middle-income states frequently falter not at the design stage, but during implementation. In South Africa, the National Health Insurance (NHI) represents one of the most ambitious post-apartheid policy reforms, aimed at advancing universal health coverage through a single-payer system. Despite sustained political commitment and extensive policy development, progress in implementing the NHI has been slow and uneven. Existing scholarship on the NHI has largely focused on financing models, constitutional debates, and health equity outcomes, with comparatively limited attention to the public administration and policy implementation conditions shaping reform feasibility. This article addresses this gap by examining the policy implementation barriers constraining the rollout of the NHI, with particular attention to governance arrangements, administrative capacity, and intergovernmental coordination within South Africa’s public sector. The study adopts a qualitative research design, drawing on document analysis and semi-structured interviews with key informants from government, civil society, academia, and the private health sector. The analysis is guided by Policy Implementation Theory and institutional perspectives to assess the alignment between policy ambition and administrative capability. The findings reveal that NHI implementation is undermined by weak policy–administration alignment, fragmented accountability across government spheres, bureaucratic inertia, uneven institutional capacity at provincial and district levels, and ambiguities within the policy and legislative framework. These constraints are further reinforced by the persistence of a dual public–private health system, which complicates coordination and operational integration. The article recommends strengthening intergovernmental coordination mechanisms, clarifying implementation authority, and investing in administrative and managerial capacity as preconditions for large-scale policy reform. It concludes that the challenges facing the NHI are primarily institutional and administrative rather than technical or financial. The study contributes to the scholarship on public administration and policy implementation by positioning the NHI as a case of implementation failure rooted in state capacity constraints, offering transferable insights for the governance of complex social policy reforms in middle-income countries.